Second shapes and measurement - Sinclair, Karleen; Anderson, Greg; Heather, Warwick (Cairo Dar el farouk, 2004)
In this book , students will lbuild on their skills in shapes and measurement , they will draw arange of shapes and objects
Arithmetic
8 12 13
Keywords: Science